Postpartum Mothers with Nipple Soreness: A Descriptive Study at East Denpasar I Community Health Center - Ni Komang Meiadi; Made Widhi Gunapria Darmapatni; Regina Tedjasulaksa; Ni Putu Melas Fitriani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Sore nipples are a common breastfeeding problem caused by trauma, often resulting from improper infant attachment during lactation. Data from the Denpasar area in 2021 showed an incidence rate of 52.8%, indicating that this condition remains a significant concern among postpartum mothers. This study aimed to identify the characteristics of postpartum mothers experiencing nipple soreness on days 6–42 after childbirth. The research employed a descriptive design with a cross-sectional approach and was conducted in May 2025 at the East Denpasar I Community Health Center. A total of 40 postpartum mothers were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using univariate analysis. The results showed that most respondents were aged 20–35 years (80%), had primary-level education (47.5%), and were multiparous (47.5%). The findings revealed that 8 respondents (20%) experienced nipple soreness, with the most common symptoms being cracked nipples accompanied by a burning sensation (20%). Other symptoms such as redness in the areola were not reported. These findings suggest that although the prevalence in this study is lower compared to previous data, nipple soreness remains a relevant issue in postpartum care. The study highlights the importance of early education on proper breastfeeding techniques provided by healthcare professionals, especially midwives. Strengthening maternal knowledge and skills can help prevent nipple trauma, reduce breastfeeding complications, and ultimately support the success of exclusive breastfeeding programs.